Amorphous Phase Mediated Crystallization: Fundamentals of Biomineralization - Wenjing Jin; Shuqin Jiang; Haihua Pan; Ruikang Tang (Crystals, 2018)
Many biomineralization systems start from transient amorphous precursor phases, but the exact crystallization pathways and mechanisms remain largely unknown. The study of a well-defined biomimetic crystallization system is key for elucidating the possible mechanisms of biomineralization and monitoring the detailed crystallization pathways. In this review, we focus on amorphous phase mediated crystallization (APMC) pathways and their crystallization mechanisms in bio- and biomimetic-mineralization systems. The fundamental questions of biomineralization as well as the advantages and limitations of biomimetic model systems are discussed. This review could provide a full landscape of APMC systems for biomineralization and inspire new experiments aimed at some unresolved issues for understanding biomineralization.